Emergencies and Public Health Crisis Management- Current Perspectives on Risks and Multiagency Collaboration - Khorram-Manesh, Amir; Burkle, Frederick M (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
The successful management of emergencies and public health crises depends on adequate measures being implemented at all levels of the emergency chain of action, from policy makers to the general population. It starts with appropriate risk assessment, prevention, and mitigation and continues to prehospital and hospital care, recovery, and evaluation. All levels of action require well-thought out emergency management plans and routines based on established command and control, identified safety issues, functional communication, well-documented triage and treatment policies, and available logistics. All these characteristics are capabilities that should be developed and trained, particularly when diverse agencies are involved. In addition to institutional responses, a robust, community-based disaster response system can effectively mitigate and respond to all emergencies. A well-balanced response is largely dependent on local resources and regional responding agencies that all too often train and operate within "silos", with an absence of interagency cooperation. The importance of this book issue is its commitment to all parts of emergency and public health crisis management from a multiagency perspective. It aims to discuss lessons learned and emerging risks, introduce new ideas about flexible surge capacity, and show the way it can practice multiagency collaboration.